Translation, Linguistic Validation, and Readability of the Spanish Version of the VISA-H Scale in Elite Athletes - Medina-Porqueres, Iván; Rosado-Velazquez, Daniel; Moya-Torrecilla, Francisco; Orava, Sakari; Cacchio, Angelo (Iranian Commission for Biomedical Sciences Journals, 2022)
Object: Data regarding the diagnosis of Proximal Hamstring Tendinopathy (PHT) is limited. There is a need for a standardized, valid, and reliable instrument for evaluating PHT among Spanish population. The purpose of this study was to linguistically validate and cross-culturally adapt the Spanish version of the VISA-H for Spanish population and to assess its readability, initial feasibility, appropriateness and acceptability. Methods: Cross-cultural adaptation was done according to established guidelines. Process included 5 steps: independent translations, synthesis of the translations, back-translations, expert committee, and pre-test. The linguistic validation of the questionnaire followed a standard methodology that included comprehension test interviews to assess the relevance, understanding and acceptability of the VISA-H. Comprehension was analyzed with cognitive interviews of 18 Spanish Professional basketball and soccer players (n = 8 male, n = 10 female end-users, healthy individuals at risk), using think-aloud and probing techniques. Results: All subjects (18/18) reported that the items were clear and did not cause upset. Additionally, every respondent had no difficulty in completing the form and found it fairly easy. No difficulties with the instructions were reported. Readability score resulted in adequate levels of understanding (Fernandez-Huerta score of 67.5), showing high level of acceptability.
Keywords: Tendones; Comprehension; Hamstring; Patient outcome assessment; Surveys and questionnaires; Tendinopathy